Analisis Kinerja Finansial Usaha Perkebunan Kelapa Sawit Rakyat di Kabupaten Pelalawan - Tarigan, Indah Sari; Hutabarat, Sakti; Tarumun, Suardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The success of a business can be measured by its financial performance. Information on financial performance is very important because it will be able to evaluate financial aspects that improve financial performance and avoid the business from the threat of bankruptcy. The objective of this study is to analyse financial performance of oil palm smallholders plantation in Pelalawan Regency. Then, a comparative study amongs different types of smallholders was also implemented. Three types of smallholder plantation are examined in this study, i.e., KKPA, PIR and Swadaya. Four financial performance indicators have been used in this analyses such as independent sample t test of profitability ratio, liquidity ratio, solvability ratio, and effectivity ratio. The results shows that the smallholders have relatively good financial performance. There is no significant difference in income between KKPA and PIR while the income is significantly different between scheme smallholders (KKPA and PIR) and Independent smallhorders.   Keyword : financial performance, profitability, liquidity, solvability, effectivity